Antimicrobial profile of Salmonella enterica serotype Choleraesuis from free-range swine in Kakamega fish market, western Kenya - David M Onyango; Violet Mmbone Ndeda; Sarah A Wandili; Sifuna A Wawire; Phillip Ochieng (Journal of Infection in Developing Countries)
Introduction: Salmonella enterica subspecies enterica serovar Choleraesuis is a host-adapted, facultative, intracellular pathogen that causes swine paratyphoid. Its antimicrobial resistance presents a challenge to feed manufacturing industries. However, stopping antibiotics in animal feed would have economic implications for the industry. Methodology: Conventional microbial methods for isolation and identification of S. Choleraesuis were employed. The isolates were subjected to screening against 17 antimicrobial agents and genotyping of resistance markers by PCR. The data were then analyzed and presented in percentages. Results: Phenotypically, 43 out of 95 isolates showed multidrug resistance. Among the 17 antibiotics tested, resistance was observed as follows: sulphonamides (45.2%), nalidixic acid (44.25%), tetracycline (42%), ampicillin (36.8%), erythromycin (34.7%), carbenicillin (31.5%), chrolamphenical (28.4%), gentamicin (27.3%), kanamycin (24.2%), spectinomycin (21%), sulfamethoxazole-trimethoprim (16.8%), streptomycin (12.6%), cephalothion (8.4%), ofloxacin (5.2%), ciprofloxacin (4.2%), and norfloxacin (4.2%). Fifty-two isolates were susceptible to the antimicrobial agents tested. A total of 3.1% of the isolates had the integron gene pattern combination of dfrA2-aadA2 (2100 bp), dfrA12 (2100 bp); 4.2% had dfrA12-aadA2-sulI (2100 bp); 2.1% had dfrA12-aadA2 (2100 bp); and 1% had dfrA2-aadA2-sulI (2100 bp), oxa1-aadA2 (1500 bp), dfrA12-aadA2-sulI, and blaPSE (2100 bp). Conclusions: The isolated S. Choleraesuis were resistant to more than 10% of the antimicrobial agents used in this study. Appropriate surveillance is warranted to gain more information about the epidemiology, as stopping antibiotics in animal feed would have economic implications for the industry.